Mechanisms of Epilepsy and Efficacy of Neuroplasticity-Based Treatment - Duan, Menghan (Transactions on Environment, Energy and Earth Sciences, 2024)
Epilepsy is a neurological disorder characterized by the development of trauma to the nervous system and recurrent seizures. Neuroplasticity, the ability of the nervous system to reorganize its structure and function in response to trauma, plays a crucial role in the development and treatment of epilepsy. Several recent studies have mentioned the potential of treating epilepsy based on neuroplasticity, such as deep brain stimulation (DBS), neurofeedback and non-invasive brain stimulation techniques. While conventional treatments focus primarily on seizure control, neuroplasticity interventions aim to alter neural circuits, reduce seizure frequency and severity, and may ameliorate the effects caused by the sequelae of epilepsy. There are already a number of therapies for epilepsy that incorporate neuroplasticity, which provides a basis for subsequent research. This paper explores the pathogenesis of epilepsy with a focus on the role of neuroplasticity in the onset and progression of epilepsy. However, further research is needed to optimize these approaches and fully understand their therapeutic potential.